1991
DOI: 10.1007/bf01887386
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the double-contrast enema for colonic polyps in patients with or without diverticular disease

Abstract: The accuracy of the double-contrast enema for the diagnosis of polypoid lesions in the presence or absence of diverticula was evaluated by retrospectively reviewing the medical records of 202 patients subjected to examination and endoscopy. Analysis of the data on 215 polypoid lesions showed that (a) the diagnostic accuracy of the examination is not affected significantly by the presence of diverticula; (b) the sensitivity of the examination is highly dependent on the size of the polyps (smaller or larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…MRI is highly accurate and reliable for prediction of the CRM [33,34]. In their most recent study of 98 rectal cancer patients, Brown et al [27] reported a 92% agreement between MRI images and histologic findings for prediction of CRM involvement. In another study assessing the tumor relationship to the mesorectal fascia, two observers independently scored the tumor stage and the distance to the mesorectal fascia on MRI and compared these observations with the final histological findings [26].…”
Section: Crmmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI is highly accurate and reliable for prediction of the CRM [33,34]. In their most recent study of 98 rectal cancer patients, Brown et al [27] reported a 92% agreement between MRI images and histologic findings for prediction of CRM involvement. In another study assessing the tumor relationship to the mesorectal fascia, two observers independently scored the tumor stage and the distance to the mesorectal fascia on MRI and compared these observations with the final histological findings [26].…”
Section: Crmmentioning
confidence: 99%
“…However, some problems remain with T stage determination on MR imaging. Overall, the agreement between MRI and histology for T staging has ranged from 66%-94% [18,[26][27][28]. One of the main problems of T staging on MRI is the distinction between T2 and T3 tumors.…”
Section: T Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic results vary according to the technical quality of this modality and the experience of the interpreter. While some ipvestigators claim that barium enema can be as sensitive and specific as optical colonoscopy, others have reported that the sensitivity achieved with barium enema can be as low as 78% in detection of polyps in the range of 5mm to 20mm in diameter [12].…”
Section: Introductionmentioning
confidence: 99%
“…Barium enema requires a great deal of physical cooperation from the patient when the X-ray radiographs of the colon are taken at different views. Additionally, its sensitivity can be as low as 78% in detecting polyps in the range of 5mm to 20mm [13].…”
mentioning
confidence: 99%